Cyclone impacts on manufacturing firms in Mozambique - Hanna Berkel; Peter Simonsen Fisker; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This study investigates how manufacturing companies were affected by tropical Cyclone Idai, which struck Central Mozambique in March 2019. The analysis builds upon a representative sample of 464 enterprises located in the cities of Beira and Chimoio which were interviewed 6 and 12 months after the natural disaster. While Beira was largely destroyed in the event, inland Chimoio was only affected to a minor degree, thus constituting our control group. Overall, we find that the cyclone had a large negative effect on income and profits, especially in the month immediately following landfall. Furthermore, the disaster hit some types of manufacturing firms much harder than others. For instance, businesses in the construction industry saw no significant decline in income, whereas micro enterprises, female-owned businesses, and tailors were among the most affected.
Keywords: O12; O14; Q54; 330; firms; natural disaster; tropical cyclone